2012
DOI: 10.4028/www.scientific.net/amr.576.761
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Strength of Weld Joint Produced by Spinning Friction Welding of Round Aluminum A6061 with Various Chamfer Angles

Abstract: Tensile strength of Aluminum A6061 joint produced by spinning friction welding (SFW) with various chamfer angles was studied. Tensile strength test specimens that have weld joint part at their centers were machined from spinning friction welded base metals. SFW specimens were prepared by making various chamfer angles of 15, 30, 45, 60, 75 degree and without chamfer angle on both contact-surfaces of base materials. It was found that chamfer angle affected tensile strength of weld joint of Aluminum A6061. Base m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…The prospect that will be opened up is the opportunity to apply this method to increase the strength of the weld joint of other metals besides aluminum. This proposed method has advantages over the conventional friction welding on aluminum, such as reported in [9,10,12,17] that produced surrounded flash at the weld joint interface that needs more time to remove the flash by machining. The proposed method can be an alternative solution to remove almost all the flash at the weld joint interface, to increase the tensile strength and to reduce the fatigue crack growth rate of the aluminum weld joint.…”
Section: Discussion Of the Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prospect that will be opened up is the opportunity to apply this method to increase the strength of the weld joint of other metals besides aluminum. This proposed method has advantages over the conventional friction welding on aluminum, such as reported in [9,10,12,17] that produced surrounded flash at the weld joint interface that needs more time to remove the flash by machining. The proposed method can be an alternative solution to remove almost all the flash at the weld joint interface, to increase the tensile strength and to reduce the fatigue crack growth rate of the aluminum weld joint.…”
Section: Discussion Of the Experimental Resultsmentioning
confidence: 99%
“…Meanwhile, the use of chamfer of the specimen as another parameter of the friction welding process to make friction welding joint between Al-Mg-Si/SiC composite can increase the strength of the CDFW joint of the Al-Mg-Si/SiC composite [8]. Besides, the geometry of the specimen, such as a double chamfer [9] or one-sided chamfer [10], could also increase the tensile and torsion strength of CDFW joints of the aluminum A6061. A smaller chamfer angle could increase the strength of CDFW joint because the use of the chamfer angle can decrease the initial friction area and reduce the mechanical heat input at the interface of the CDFW joints.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Kekasaran permukaan kontak dan geometri permukaan kontak yang bersudut chamfer, berpengaruh pada temperatur proses, bentuk geometri flesh, dan kekuatan tarik sambungan paduan aluminium A6061 pada pengelasan gesek continuous drive [6]. Geometri permukaan gesek berbentuk kerucut pada kedua bidang kontak, dengan sudut chamfer 30 0 , menghasilkan sambungan dengan kekuatan tarik maksimum pada pengelasan gesek continuous drive A6061 [8].…”
Section: Waktu Tempa (Forging Time)unclassified
“…There have been many studies on continuous drive friction welding (CDFW) in combining aluminum alloys, for example, A6061 which possesses good corrosion resistance, medium tensile strength, and good welding characters in many applications such as in cars, airplanes, and trains. One study analyzed the tensile strength of the welded joints generated by the rotating friction welding of spherical aluminum A6061 with different chamfer angles [2]. The result reported that the angle of the chamfer affects the tensile strength of A6061 rotating friction welding joint with the 30-degree chamfer angle giving the maximum tensile strength.…”
Section: Introductionmentioning
confidence: 99%